Covid-19 impact on micro, small, and medium-sized enterprises under the lockdown: Evidence from a rapid survey in the Philippines - Shigehiro Shinozaki; Lakshman Nagraj Rao (Asian Development Bank Institute (ADBI), 2021)
The novel coronavirus disease, COVID-19, has brought significant change to people's lives and business activities nationally, regionally, and globally. The Philippines took swift action-including enhanced community quarantine (ECQ)-to contain the pandemic and launched an emergency subsidy program with massive public spending to support disrupted households and businesses. The strict lockdown ran from mid-March to the end of May 2020 in the national capital region and high-risk provinces, causing huge economic losses. Six months after the March lockdown, the Philippine economy has moved to the recovery stage, but micro, small, and medium-sized enterprises (MSMEs) are continuing to confront a sharp drop in demand and revenue. This paper examines the initial impact on MSMEs of the ECQ and lockdown measures using evidence obtained from a rapid nationwide survey conducted from the end of March to mid-April 2020 and derives policy implications.
Keywords: D22; G20; L20; L50; 330; COVID-19; economic crisis; economic impact; MSMEs; SME development; access to finance; SME policy; Philippines